ATRIBUSI KOMUNIKASI PADA KESTABILAN EMOSIONAL MAHASISWA FAKULTAS ILMU BUDAYA UNIVERSITAS HASANUDDIN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research describes communication attribution and emotional stability among students at the Faculty of Cultural Sciences, Hasanuddin University. Using qualitative field research methods and a phenomenological approach, the study collected data through observation, interviews, and student documentation. The data were analyzed in four stages: data collection, data presentation, data reduction, and conclusion drawing. The results indicate that interpersonal communication practices among new students play a crucial role in sharing feelings, receiving social support, and maintaining emotional stability. Communication serves as a primary tool for connecting, responding, and openly discussing feelings and issues. This study highlights the importance of effective communication in supporting adaptation and emotional stability for new students in an academic environment. Communication attribution is also related to decision-making, character changes, and behavioral consistency of students, influenced by both internal and external factors. The implications of this research include encouraging students to communicate openly and seek social support, as well as enhancing mental health support initiatives to prevent emotional issues. Implementing effective communication, collaborating with mental health agencies, and developing university policies that support student well-being are crucial steps in supporting the findings of this study.